PERLINDUNGAN HUKUM BAGI PEKERJA YANG TERKENA PEMUTUSAN HUBUNGAN KERJA DIMASA PANDEMI COVID-19 (Studi Penelitian Supermarket Brastagi Kota Medan Provinsi Sumatera Utara) - Tiara T; Nasrianti N; Nurarafah N (Fakultas Hukum Universitas Malikussaleh, 2021)
Now, all countries including Indonesia are being hit by the Covid-19 virus, this can be seen by many companies experiencing financial difficulties, then encouraging employers to issue several policies that are detrimental to their workers, namely Termination of Employment to improve the efficiency of their companies on the grounds of Covid-19 . However, workers affected by this layoff do not get their rights (salary, severance pay) as happened at the Berastagi Supermarket, Medan City. The purpose of this research is to find out how to apply the legal protection provided to workers who have been laid off, the obstacles that are a barrier to obtaining workers' rights, and what efforts must be taken. The type of research method used in this research is using empirical juridical or sociological juridical research methods, namely research procedures that aim to obtain legal knowledge empirically by going directly to the object. Legal protection for workers aims for justice so that employers do not arbitrarily do something, there were 60 workers who were laid off during the covid pandemic at the Brastagi Supermarket, field results show that legal protection for these workers has not been going well, there should be clarity regarding this matter in accordance with Law no. 11 of 2020 concerning Job Creation Articles 151 to 154 where employers may perform layoffs without agreement and reasons, because it is clearly regulated in article 154(A). Suggestions for employers should not make decisions unilaterally, it is also recommended for the Manpower Office to more often supervise companies that do not follow the rules, and suggestions for workers to be more concerned about the rights and obligations of workers. Keywords: Legal Protection, Termination of Labor, Covid-19 Pandemic